The principle of natural correspondence in the philosophical and pedagogical heritage of J.A. Comenius in the perception of S. Rusova and the authors of the text - Ganaba, Svetlana Oleksandrivna; Bakhmat, Nataliia Valeriivna (Siedleckie Zeszyty Komeniologiczne seria Pedagogika, 2019)
On this article is to emphasize the heuristic potential of the natural correspondence ideas of J.A. Comenius in the philosophical and its importance for the pedagogy of Ukraine in the present times. The urgency of the topic chosen is caused by the fact that during the years of total com-munist ideology domination in the Ukrainian society there was an endless struggle against the scientific free-thinking, the original creative thought was destroyed and distorted, the history of its formation and development was suppressed and falsified. It is possible to restore the lost cultural heritage and the broken connection of generations only if each creator of our intellectual and cultural heritage is returned to the Motherland. In works J.A. Comenius developed the principle of the nature conformity, previously proposed. He presented it as free development of the child's potential and abilities. The organic unity of a person and nature considered the natural state of the child's personality, which should become the solid foundation of educational activity. In education a person is seen neither as a way of implementing certain educational projects, nor as an instrument of manipulation, but as a goal, as an active subject capable to create an understanding of the world around and, at the same time, to defend his own unique identity. J.A. Comenius’ idea connected with the principle of nature correspondence is the understanding of a person as a world in a diminished forms that is as a peculiar Microcosm. The researchers reveal a concept of a holistic personality. The integrity of the individual the scientists understands as the process of accumulation of the natural and socio-cultural environment properties within a person, and analyzes it in two dimensions: psychophysiological and sociocultural. The ideas of great pedagogical thinkers highlighted in the article are consonant with the present and are of great importance for the education system reformation and the creation of a new Ukrainian school.